Utilization of Digital Marketing in Increasing Sales of Msme in Bengkalis Regency: Case Study on Msme of Martabak Mandor Gatot Subroto Street Bengkalis City - Juspiani Juspiani; Yunelly Asra (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This research project aims to utilize digital marketing to increase sales of Msme Martabak Mandor, Gatot Subroto street, Bengkalis City. Project implementation is carried out through 4 stages, namely (1) project preparation planning (2) project implementation planning, third (3) project completion stage, and Fourth(4) Project Reporting Plan. Digital marketing used is email marketing and social media marketing. The results of this project were From implementing of digital marketing, the sales of Sweet Martabak and Egg Martabak products per October are 2132 boxes. With 1677 boxes of Sweet Martabak products and 455 boxes for Egg Martabak. With a total sales turnover of Rp.37,763,000. In November, sales of Sweet Martabak products total 1532 boxes and 418 boxes of Egg Martabak with a total sales turnover of Rp.37,839,000. MSME Martabak Mandor experienced an increase in sales revenue of 27.9%. This also proves that the implementation of digital marketing is able to increase sales of MSME Martabak Mandor .The average increase is 2-3 boxes of each Martabak product sold consumers are interested in ordering online and repurchasing outside the Bengkalis city area and Gatot Subroto Street, and there are also people or consumers who come directly to the Msme Martabak Mandor place.